The Effect of Radiometric Resolution on Information Sharing Between Landsat8 Bands (University of Khartoum Engineering Journal, 2023)
The technological revolution that the world is witnessing also included the development of the characteristics of remote sensing devices, which had a direct impact on increasing the accuracy of the data obtained through these devices. For example; the radiometric resolution of Landsat satellite sensors increased from 7 bits in the first Landsat sensors to 16 bits in Landsat-8. In this study, the effect of this improvement in radiometric resolution was measured to find the amount of change in the mutual information at several dynamic ranges. The study area was the state of Khartoum, and the study was conducted on four different types of land cover (agricultural, urban, water, and desert) to determine the amount of shared information between several dynamic ranges based on the land cover unit. The image obtained from the Landsat-8 satellite for the study area had a 16-bit dynamic range. However, it was down sampled to 8bits, 9 bits, 10 bits, 11 bits, 12 bits, 13 bits and 14 bits, and the amount of information shared between these dynamic ranges and the original image was calculated for the first seven bands of Landsat-8. The results showed that the amount of shared information varies based on the type of land cover, however, this amount reaches its lowest value on the water cover between the 8-bit image and the 16-bit image which is 80%. The study ended with a recommendation that the effect of change in radiometric resolution should be examined in the stage classification of images.